Delineating the fuzzy front end of market shaping - Kindström Daniel; Makkonen Hannu; Kaartemo Valtteri (Elsevier, 2025)
Emerging perspectives define markets as continuous, malleable processes that can be shaped through various activities. In this research, the authors address the early phase of such market-shaping processes, developing a conceptual framework and linking the front-end phase to an overall market-shaping process. We propose and develop a fuzzy front end (FFE) concept centered around the market image to reflect market shaping's less organized and more exploratory early phase.
Nine propositions outline this critical phase and its fundamental dimensions, roles, and characteristics. Finally, by outlining the FFE of market shaping, this article reveals future research directions for elaborating on the concept.